A Comparative Study on the Diagnostic Value of Conventional Spin Echo Proton Density and Fast Spin Echo Proton Density Sequences of Magnetic Resonance Imaging in Diagnosis of Meniscal Tear - Farhad Nalaini; Mahdi Mohammadi; Somayeh Mahdavikian; Nazanin Farshchian (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background & Objectives: Knee is the largest synovial joint in the body. Although FSE PD (fastspin echo proton density) imaging technique for the diagnosis of meniscal tear has replaced CSE PD(conventional spin echo proton density) technique in many MRI centers, several studies have questionedthe effectiveness of FSE PD technique in diagnosis of meniscal tear. In this study, the diagnostic valuesof CSE PD and FSE PD techniques in evaluation of meniscus tear are compared.Materials: In this study, using CSE PD and FSE PD techniques, MRI was performed on 67 knees ofpatients with suspected meniscal tear referring to the MRI Center of Imam Reza Hospital (Kermanshah,Iran). Diagnostic arthroscopy was also performed for all patients. The data were entered SPSS version20, and finally the results of MRI reports of the two techniques were compared in evaluation of meniscaltear taking into account the arthroscopic findings as the gold standard.Results: According to the results of this study, no significant difference was found in specificity andpositive predictive value of the two techniques. However, the sensitivity and negative predictive valueswere significantly different, in such a way that the related values were 97% and 97% in the CSE PDtechnique and 69% and 73% in the FSE PD technique, respectively.Conclusion: Due to low sensitivity and high false negative results, MRI using FSE PD technique is notrecommended as an alternative for CSE PD technique in evaluation of meniscal tear.